2006
DOI: 10.1080/15533170600651520
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Iron(III) Hydroxide on Aggregations of Several Proteins

Abstract: We have found that deposition of the iron(III) hydroxide occurred rapidly on the aggregates of amyloid beta-peptide (1-40), transferrin, and albumin induced by zinc(II) chloride in the solution containing iron(III) compounds with amino acid derivatives; the deposition of iron(III) hydroxide may proceed via the coordination of nitrogen and oxygen atoms of the amino acid residues of the aggregated proteins to the iron(III) ion, implying that iron(III) compounds with amino acids or peptides in plasma, so-called "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We have found that deposition of iron(III) hydroxide occurs readily on the aggregates of amyloid beta-peptide [abbreviated as Ab ] by the addition of zinc(II) chloride to the solution containing iron(III) compounds with nta, edda, and other amino acid derivatives [72]. This implies that iron(III) compounds with amino acids or peptides in plasma may be an intrinsic iron(III)-ion carrier to induce the high level accumulation of iron(III) ions in the amyloid deposits.…”
Section: The Examples Of Ntbi Modelsmentioning
confidence: 99%
“…We have found that deposition of iron(III) hydroxide occurs readily on the aggregates of amyloid beta-peptide [abbreviated as Ab ] by the addition of zinc(II) chloride to the solution containing iron(III) compounds with nta, edda, and other amino acid derivatives [72]. This implies that iron(III) compounds with amino acids or peptides in plasma may be an intrinsic iron(III)-ion carrier to induce the high level accumulation of iron(III) ions in the amyloid deposits.…”
Section: The Examples Of Ntbi Modelsmentioning
confidence: 99%